Dielectric characterization of rapeseed (Brassica napus L.) from 10 to 3000 MHz. (March 2016) - Bansal, Namita; Dhaliwal, Amarjit S.; Mann, Kuldip S.
Abstract : Dielectric characterization of rapeseed ( Brassica napus L.) in the temperature range of 20–60 °C and at moisture contents of 8.5, 12.5 and 16% wet basis (w.b.) was performed by determining the dielectric constant and loss factor at frequencies from 10 to 3000 MHz. This range of frequencies includes the ISM (Industrial, Scientific and Medical) frequencies of 13, 27, 40, 915 and 2450 MHz. An open-ended coaxial probe (Speag DAK, 12) and a vector network analyzer (Agilent Technologies, E5071C) were used to measure the dielectric properties (dielectric constant and loss factor). Compressed ground samples of rapeseed at densities nearly equivalent to seed density were used. Determined data at the ISM frequencies was fitted to polynomials to represent the dependence of the dielectric constant as well as the loss factor on temperature and moisture content. The calculated penetration depth of the electromagnetic field in rapeseed at the ISM frequencies shows that at a given moisture content and temperature, it decreases with increasing frequency. The reported data are useful in designing and developing radio-frequency (RF) and microwave (MW) applicators for dielectric heating of rapeseed. Highlights: Dielectric properties of rapeseed in frequency range 10–3000 MHz. Measuring system consists of coaxial probe (Speag DAK 12) and VNA (Agilent E5071C). Polynomial fitting of the determined data of the dielectric properties. Strong influence of frequency, moisture content and temperature on penetration depth.